Inskripsi Ashabul Kahfi pada Mihrab Masjid Agung Surakarta - Haris, Tawalinuddin (SUHUF, 2012)
The Great Mosque of Surakarta is among the old mosques in Java that served as a royal mosque. The employees of the mosque were appointed by the Susunan of Surakarta and granted positions as courtiers. Since October 1, 1948, the management of the Great Mosque has been under the Ministry of Religious Affairs as stated in the Regulation of the Minister of Religious Affairs, dated on January 18, 1947 No. 3/1947 concerning the finanical resources of the Great Mosque. Above the Mosque’s mihrab there is found the relief of a tughra, crown, and a number of Arabic inscriptions, including the names of figures who remind us of the names of the sleepers in the story of the Cave Dwellers (Ashab al Kahfi).